O conhecimento histórico após a BNCC e o Novo Ensino Médio: mudanças e permanências de uma disciplina escolar - Cardoso, Maria Auriene (2024)
This research investigates the changes and the continuation in History teaching after the approval of the National Common Curricular Base (BNCC) and the Reform called New High School (NEM). The research starts from the reading key that associates these educational reforms with neoliberalism (LAVAL, 2019). It is also important for this research to analyze the “narrative warfare” around the History curriculum (LAVILLE, 1999), to investigate the conflicts and conceptions of History teaching, brought to the midst of debates about reforms and the concept of disciplinary code (FERNÁNDEZ, 1997) to think about the changes and the permanencies in History teaching. An investigation was carried out into the documentation that instituted the reforms, such as Law No. 13,415/2017 (High School reform), texts from the 1st, 2nd and 3rd versions of the BNCC and the DCRC (Ceará Reference Curricular Document). The research was carried out using quantitative and qualitative methodology, using a questionnaire, with 50 answers; 6 interviews with High School History teachers from the Ceará state schools network. Among the results, it was found that the reforms studied affect teachers in different ways, depending on the school model and the teacher's stability in the education network and at the school. 92% responded that they notice changes in history teaching, caused by the reduction of the workload, which leads to increasingly larger cuts by teachers, the lack of rganization of content by grade, the organization of content by skills and abilities and the absence of a History book. However, the teachers also state that they feel more autonomy to choose the contents after the reforms (18%) and 78% stated thatw although they feel negative impacts, they are able to maintain autonomy in their teaching practices.